Aliens will provide: Avian responses to a new temporal resource offered by ornithocorous exotic shrubs - Vergara Tabares, David Lautaro (2018)
Frugivorous birds are able to track spatiotemporal changes in fruit availability. Food resource fluctuations, characteristic of seasonal environments, can be affected by the naturalization of exotic ornithocorous plants. In the mountain forest of central Argentina, invasive shrubs of the genus Pyracantha provide a new temporal resource that modifies fluctuations of natural resource availability because the invasives fructify in autumn–winter (largely uncoupled with the fruiting of native species). The contrasting patterns of resource fluctuation between non-invaded and invaded areas throughout the year provide a good study system to test predictions of the fruit-tracking hypothesis, and to understand the relationship between food resources offered by fleshy fruited invasives and abundances of avian trophic guilds. By means of point counts conducted during five time periods at invaded and non-invaded sites we found that the presence of Pyracantha, and time periods, significantly affected frugivorous bird abundance, which in autumn–winter was greater in invaded sites and in spring–summer similar between invaded and non-invaded sites. On the other hand, granivores and insectivores did not show a significant relationship with the presence of Pyracantha. Abundances of the most common seed disperser were significantly affected by the interaction between time period and presence of Pyracantha. These results indicate that the abundances of birds that legitimately disperse Pyracantha seeds are temporally and spatially associated with fruit abundance provided by this exotic plant. This underscores fruit availability as an important ecological factor affecting frugivorous bird abundance, and suggests that Pyracantha seed dispersers are capable of detecting changes in the availability of its fruit, likely contributing to the effectiveness of its dispersal.